Genetic architecture of adult-plant resistance to stripe rust in bread wheat (Triticum aestivum L.) association panel - Atsbeha, Genet; Mekonnen, Tilahun; Kebede, Mulugeta; Haileselassie, Teklehaimanot; Goodwin, Stephen B.; Tesfaye, Kassahun (Frontiers in Plant Science, 2023)
Stripe rust, caused by Puccinia striiformis f. sp. tritici, is a severe disease of wheat worldwide, including Ethiopia, causing up to 100% wheat yield loss in the worst season. The use of resistant cultivars is considered to be the most effective and durable management technique for controlling the disease. Therefore, the present study targeted the genetic architecture of adult plant resistance to yellow rust in 178 wheat association panels. The panel was phenotyped for yellow rust adult-plant resistance at three locations. Phonological, yield, yield-related and agro-morphological traits were recorded. The association panel was fingerprinted by the genotyping-by-sequencing (GBS) platform, and a total of 6,788 polymorphic SNPs were used for genome-wide association analysis to identify effective yellow rust resistance genes. The marker-trait association analysis was conducted using Genome Association and Prediction Integrated Tool (GAPIT). The broad-sense heritability for the considered traits ranged from 74.52 to 88.64%, implying the presence of promising yellow rust resistance alleles in the association panel that could be deployed to improve wheat resistance to the disease. The overall linkage disequilibrium (LD) declined within average physical distance of 31.44 Mbp at r 2 = 0.2. MTA analysis identified 148 loci significantly (p = 0.001) associated with yellow rust adult-plant resistance. Most of the detected resistance QTLs were located on the same chromosomes as previously reported QTLs for yellow rust resistance and mapped on chromosomes 1A,